PENGARUH EMOTIONAL INTELLIGENCE DAN WORK LIFE BALANCE TERHADAP INDIVIDUAL PERFORMANCE DENGAN SATISFACTION WITH LIFE SEBAGAI VARIABEL MEDIASI - Shafa Wisista Aprilia Putri; Sidiq Permono Nugroho (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to analyze the effect of emotional intelligence and work-life balance on individual performance with satisfaction with life as a mediating variable. This research method is quantitative. The population in this study is employees among Generation Z (1997 – 2012) in Solo Raya. In this study, sampling techniques were used with Non-Probability Sampling techniques. The sample size of this study was 105 respondents. This research data collection technique uses questionnaires. This analysis process is carried out using the Smart PLS 3 application. The result of this study is that Emotional intelligence and Work-life balance have a significant positive effect on satisfaction with life. Satisfaction with life, Emotional intelligence, Work-life balance has a significant positive effect on individual performance. Emotional intelligence has a significant positive effect on individual performance through one of the components of subjective well-being, namely life satisfaction as mediation. Work-life balance has a significant positive effect on individual performance through one of the components of subjective well-being, namely life satisfaction as mediation